GAMBARAN FASILITAS LABORATORIUM BOGA PADA MATA KULIAH PRAKTIKUM GASTRONOMI MAHASISWA AKADEMI KESEJAHTERAAN SOSIAL ”AKK’’ YOGYAKARTA - Yhoga, Waras Dwi; Karyaningsih, Endang Wani; Kusuma Wati, Ika Wahyu (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This study aims to determine the description of food laboratory facilities in the gastronomy course of AKS-AKK Yogyakarta students from laboratory standard indicators, facilities and infrastructure standards. This research is a quantitative descriptive research with a survey method. The population in this study was students of the culinary arts study program who took gastronomy courses as many as 39 students. This study used saturated samples. The sampling technique takes the entire population as a sample so this study is a population study. Data collection method using questionnaires. Test this instrument using trials. The results showed that the description of food laboratory facilities in the high category with a frequency of 43.6% was mostly located in the range of scores between 136-147 as many as 10 students (25.6%); In laboratory standard indicators, the medium category was obtained with a frequency of 64.1% with the most interval range with a score of 31-34 as many as 17 (43.6%); In the standard indicator of food laboratory infrastructure facilities in the high category with a frequency of 48.7% with the most interval range with a score of 112-120 as many as 13 (33.3%).